The Effect of Tourist, Tourism Object, GRDP, Populations on Local Own-Source Revenues of Yogyakarta Province - Galih Pratama Putra; Nenik Woyanti (EKO-REGIONAL, 2023)
Yogyakarta is the region with the lowest PAD among other provinces on the island of Java. This province is one of the tourist destinations because there are many tourist destinations. This province has many objects and tourist attractions so the intensity of tourists visiting is very high. This has the potential to increase revenue sources through tourism. This study aims to analyze the effect of the number of tourists, the number of tourism objects, GRDP, and the number of residents on local revenue (PAD) in the Special Region of Yogyakarta. The independent variables used in this study are the number of tourists, the number of tourism objects, GRDP, and the number of residents. The dependent variable used in this study is original regional revenue (PAD). The data used in this study is secondary data obtained from the Central Statistics Agency, BAPPEDA, and the Tourism Office in the form of panel data, with the object of research being 5 districts/cities in the province of D.I Yogyakarta with the period 2011-2020. This study uses a quantitative analysis method completed with a panel data regression analysis tool Fixed Effect Model (FEM) with Cross-Section SUR weighting. Based on the results of the regression, it is known that the variable number of tourists and GRDP has a positive and significant influence on Regional Original Income. However, the variables of the number of tourism objects and the number of residents have no effect on the Regional Original Income of the Special Region of Yogyakarta.